Herlyn-Werner-Wunderlich (HWW) syndrome with kyphoscoliosis: a rare urogenital anomaly in a teenage girl. Issue 3 (22nd March 2021) - Jhirwal, Manisha; Singh, Pratibha; Sharma, Charu; Khera, Pushpinder
Abstract : The obstructed haemivagina with ipsilateral renal agenesis (OHVIRA) syndrome also known as Herlyn-Werner-Wunderlich syndrome, a rare congenital malformation in females, results due to developmental abnormality in the müllerian duct. We are reporting a case of a 14-year-old girl who presented with pain and a lump in abdomen for the last 5 months. The MRI abdomen and pelvis confirmed the diagnosis of OHVIRA syndrome. The patient underwent haematocolpos and haematometra drainage, followed by vaginal septum resection.